Pengaruh January Effect Terhadap Return Saham Pada Perusahaan Sektor Farmasi Di Bursa Efek Indonesia Periode 2020–2024 - Arsenio, Dany; Carmidah; Apridasari, Esty; Dwi Swandini, Witantri (Prodi Akuntansi, Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2026)
This study examines the effect of the January Effect on stock returns of pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period, incorporating the market return of the Indonesia Composite Index (IHSG) as a control variable. The research employs a quantitative approach using multiple linear regression analysis on 300 observations derived from five companies selected through purposive sampling. Stock returns are calculated using realized returns based on monthly closing price changes, while the January Effect is proxied using a dummy variable. The results indicate that the regression model is statistically significant at the 5% level (Sig. F = 0.031). Partially, the January variable has a significant negative effect, indicating that stock returns in January tend to be significantly lower compared to other months. Meanwhile, market return does not have a significant influence on stock returns. These findings suggest that the January Effect is contextual and does not consistently follow the classical pattern of higher January returns, particularly within the pharmaceutical sector during crisis and post-pandemic periods.